Ferroptosis, DNA damage repair, and transporter proteins: associated with platinum sensitivity and prognosis in epithelial ovarian cancer - Mai Gao; Xuan Feng Wang; Qian Long; Dan Yang; Hong Zhu; Jun Zhu (Molecular Biology Reports, 2026)

Flexural performance and calculations of concrete-encased square concrete-filled steel tubular (CFST) hybrid structures - Dan-Yang Ma; Jie Gong; Lin-Hai Han; Long-Hui Du (Engineering Structures, 2026)

Performance enhancement of hollow-structured H2TiO3 lithium ion sieve induced by Nb doping modification: High structural stability and superior adsorption capability - Nai-Cai Xu; Jing Liu; Dan-Dan Shi; Yi-Ying Wang; Jian-Long Zheng; Cai-Ying Zhao; Kai-Peng Zhong; Jia-Jia Cao; Shao-Ju Bian (Hydrometallurgy, 2026)

Vortex bionic structural composites fabricated by DLP 3D printing with high electromagnetic shielding effect and thermal conductive property - Jingxing Gui; Tao Zhang; Sha Long; Yingtao Li; Feiyue Zhou; Yuxuan Ma; Yuting Xue; Xueting Xu; Chunyan Hu; Baojiang Liu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

137Cs and 210Pbex dating to assess sedimentation rates in terraced valley floor fields - Yunqi Zhang; Shucui Liu; Dan Li; Wei Li; Qingfang Tan; Yi Long; Guirong Hou; Ziteng Luo; Haiyan Yi; Yong Wang; Bo Tan (Journal of Hydrology, 2026)

Machine learning prediction and analysis for LFL of C0-C2 combustible gases and blends under wide operating conditions - Mingkun Zhang; Wenchao Zhu; Dan Shen; Xiangyu Meng; Wuqiang Long; Mingshu Bi (Journal of Cleaner Production, 2026)

A fluorescent/photochromic dual-function Mo-based hydrogel for information encryption - Sha Long; Yanghang Liu; Jingxing Gui; Yuting Xue; Yuxuan Ma; Baojiang Liu; Chunyan Hu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Resilient bioconversion of nitrite-rich organic wastes by black soldier fly larvae: Detoxification mechanisms and microbiome-mediated nitrogen cycling - Chaowei Qin; Mengjun Long; Jiabao Chen; Dan Shao; Shanshan Zhao; Long Chen; Zhenyu Zhang; Lijun Duan; Huan He; Juan Cortes Ortiz; Hui Wei; Qing Li; et al. (International Biodeterioration & Biodegradation, 2026)

Anchoring MoOx nanodots in N-doped porous carbon via a biomimetic strategy: enhanced supercapacitor performance - Li Li; Shou-Cheng Jiao; Chang-Wang Shao; Yu-Man Li; Long-Yu Zhang; Xing-Shun Cong; Xian-Yong Wei; Dan Mu (Fuel, 2026)

Lapatinib Induces Ferroptosis in Cardiomyocytes by Regulating ATF4/GPX4 - Yue Sun; Keyi Jiang; Dan Wang; Chunlei Li; Yuqing You; Long Chen; Wei Chang; Liwei Zhang; Hongqi Feng; Dandan Li; Yilan Li (Cardiovascular Toxicology, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Experimental behaviour of concrete-encased square concrete-filled steel tubular (CFST) hybrid structure subjected to axial compression - Dan-Yang Ma; Long-Hui Du; Lin-Hai Han (Engineering Structures, 2026)

Temperature-adaptive flexible pressure sensor based on thiol-ene click chemistry and 3D printing for wearable devices - Feiyue Zhou; Lixuan Yang; Shuqi Zhang; Yuxuan Ma; Yingtao Li; Sha Long; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Ecological-health risks and priority control factors in acid mine drainage-impacted mining regions: A lifecycle assessment from a source-oriented perspective - Bing Wang; Lei Ma; Jiazhong Qian; Yang Long; Wei Xie; Dan Ding; Hekun Yang (Environmental Impact Assessment Review, 2026)

A T4SS effector directly disarms competing antibacterial T6SSs by hijacking their conserved spike component - Dan Xiong; Jinxing Liao; Zhiyuan Zhang; Julien F. Giraud; Xiuyuan Li; Dongjing Cheng; Bingxin Wang; Limin Wang; Xiaolong Shao; Long Lin; Jinshui Zheng; Xiangyang Li; et al. (Science China Life Sciences, 2026)

Engineering phosphoribosylpyrophosphate synthetase in Methylobacterium radiotolerans for lettuce growth and quality enhancement - Long-Yu Zhang; Dan-Dan Tian; Zhe Liu; Ming-Ming Zhang; Jing Wu; Shuai-Jie Wang; Song Yang; Cong Zhang; Lu Yao; Ling-Ling Tan (Archives of Microbiology, 2026)

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Molecular switch engineering manipulates Zn ion transfer enabling fast charging Zn-ion batteries - Yuying Li; Qing Xin; Pan Feng; Junnan Qu; Jingxuan Ren; Jiahao Lei; Jinhao Chen; Jingyao Li; Renming Liu; Xintao Long; Xinli Guo; Dan Luo; et al. (Chemical Engineering Journal, 2026)

Alpha -Glucosidase inhibitory activity and molecular docking analysis of a new biflavan isolated from Impatiens macrantha - Duc Long Le; Ba Thi Cham; Thi Yen Tran; Ha Nguyen Xuan; Ngoc Binh Vo; Nguyen Thi Le Huyen; Tran Ngoc Dan Thanh; Do Van Truong; Quoc Anh Ngo; Nguyen Thi Thuy Linh (Natural Product Research, 2026)

Novel dual-phase porous Mn2O3/(Co,Mn)(Co,Mn)2O4 composite cathode material with enhanced interfacial stability for ultra-long cycle life in zinc ion batteries - Haoran Wang; Zhaoxia Hou; Hui Zhang; Wensheng Zong; Shuting Yin; Haibo Long; Zhongchao Fu; Nan Wu; Zihui Zhai; Depeng Zhang; Fanshun Meng; Dan Zhou (Chemical Engineering Journal, 2026)

Recent understanding of crosstalk between muscle and different organs in regulating freshwater fish flesh quality under stress condition: A review - Liwen Wu; Liangzi Zhang; Ling Peng; Yong Long; Guili Song; Soottawat Benjakul; Juan You; Ru Liu; Qilin Huang; Huawei Ma; Dan Jia; Tao Yin (Aquaculture, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

How does the hypocotyl contribute to the early growth stage of Zostera marina seedlings ecologically? - Yan-Hao Zhang; Jin-Ji Liu; Yan Sun; Zhen Zhang; Dan Huang; Qing-Gang Long; Wen-Jie Yan; Pei-Dong Zhang (Journal of Environmental Management, 2026)

Decontamination of volatile compounds from post-consumer recycled HDPE via supercritical CO2: Unravelling the critical role of co-solvent molecular structure - Ming-Yue Zhang; Qi-Zhi Su; Can Xu; Tian-Long Zhang; Huai-Ning Zhong; Qin-Bao Lin; Dan Li; Ben Dong (Waste Management, 2026)

Unlocking the potential of high-entropy catalysts in selective electrocatalytic organic transformations - Meng Dan; Yu-Qi Zhang; Tao Wei; Run-Long Qi; Shishan Xue; Zhen Guo; Zhao-Qing Liu (Science Bulletin, 2026)

Efficient production of medium-chain fatty acids in engineered Escherichia coli strains from ionic liquids pretreated bamboo enzymatic hydrolysate with carbon dioxide fixation - Ling Zhou; Kun Rong; Kai-Xing Xiao; Ruo-Shi Luo; Zhao Qin; Rustam Iqra; Xia Fang; Jikai Zong; Zhiyao Peng; Min Long; Dan Wang (Bioresource Technology, 2026)

Phylogenomics of an early-branching clade of Orthocladiinae (Diptera: Chironomidae) - Hai-Feng Xu; Zhi-Chao Zhang; Dan Zhang; Viktor Baranov; Chen-Hong Li; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

From waste to wellbore reinforcement: Assessment of quartz tailings functionalization in oil well cement under simulated HTHP conditions - Feng Zhao; Xueling Zeng; Dan Long; Kaiyuan Mei; Chunmei Zhang; Gaoyin Zhang; Xiaowei Cheng (Environmental Research, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A data-driven investigation on PM2.5 dispersion and the relevant professional driver exposure risks induced by compound turbulence in street canyons - Jiawei Ding; Dan Mei; Mingwei Gao; Yingmin Yan; Tianhe Long; Heng Song (Urban Climate, 2025)

The role of mobility and air-conditioning in prenatal temperature exposure and birth outcomes: A prospective birth cohort study in Guangzhou - Yuye Jiang; Xin Chen; Shuhua Chen; Yuyuan Bu; Zhenghong Zhu; Dan Long; Huailin Wang; Maimaitiminjiang Wulayin; Jingjin Gong; Xiaoxin Zhang; Cunrui Huang; Jian Hang; et al. (Environmental Research, 2025)

Optimization of dielectric microwave response of MoS2 through human-machine interaction based on d-d orbital modulation phase engineering - Long Ma; Yunfei He; Sihao Dou; Zhiyuan Dan; Minghao Yang; Long Xia; Dongdong Liu; Bo Zhong; Xiaoxiao Huang (Chemical Engineering Journal, 2025)

BreathFIT: Liquid metal-PDMS sticky conductors and AuNPs/MXene biosensors for synchronous EMG-lactate monitoring in respiratory health - Yang Liu; Zixin Lin; Yuetao Zhang; Xinyu Zhang; Zhiqi Li; Rubing Xiong; Chunxiao Long; Jiaqi Huang; Can Liu; Ziwei Zheng; Dan Li; Yongchang Ouyang; et al. (Chemical Engineering Journal, 2025)

Performance enhancement strategies for lithium-based battery electrodes via covalent organic frameworks: A review of recent advances - Waheed Ahmad; Muhammad Tahir; Batoul Bibi; Liang He; Hui Tang; Longbing Qu; Fazal Ul Nisa; Mizna Naseem; Habib Ullah; Iram Abdul Ghafar; Saira Manzoor; Yihao Long; et al. (Chemical Engineering Journal, 2025)

Unveiling the oxidation-reduction mechanism of the Arsenazo III-U(VI) complexes by synergistic electron beam irradiation and Cu-Fe MOFs: Combined kinetic and DFT studies - Ruirui Wang; Xiaomao Zhou; Dan Liu; Jiahui Li; Long Zhao; Zhen Dong; Buri Qi; Miao Yang (Chemical Engineering Journal, 2025)

Link between Double-Diffusive Staircases and Water Masses in the Arctic Ocean - Xue-Long Song; Sheng-Qi Zhou; Ling Qu; Yuan-Zheng Lu; Lu-Dan Pan (Thalassas: An International Journal of Marine Sciences, 2025)

Fenton-modified agricultural waste kenaf as an adsorbent for arsenic removal from wastewater: Material preparation, removal process and mechanism - Hua Long; Xin Xu; Ju Luo; Kui Liu; Changya Chen; Wang Yu; Dan-dan Liao (Process Safety and Environmental Protection, 2025)

Post-collisional crustal evolution in the central Lhasa block of southern Tibet: Insights from early and late Cretaceous magmatism - Shu-Ya Huang; Lu-Lu Hao; Qiang Wang; Andrew C. Kerr; Wan-Long Hu; Qing-Qing Mo; Mao-Rui Liu; Yue Qi; Wei Dan; Xiu-Zheng Zhang (Lithos, 2025)

A novel hierarchical porous 2.5D electrode system with molecular sieve based particles: Towards efficient electrochemical oxidation of various pollutants by a single-pass process - Dan Shao; Hao Wang; Weipeng Zhao; Yang Liu; Jikun Zhang; Jiale Zhang; Tiantian Zhao; Long He; Hao Xu; Xiaohua Jia; Haojie Song (Journal of Hazardous Materials, 2025)

3D excitation-emission matrix (EEM) fluorescence-based efficient detection of cosmetics health risks: comparative AI algorithm and eXtreme Gradient Boosting (XGBoost) implementations - Runbao Du; Te Bu; Zhenchuan Huang; John Donald Morley; Yukun Xing; Meixuan Li; Hao Xu; Yuzhang Feng; Xinjie Zhou; Dan Long; Zhengyu Jin (Journal of Cleaner Production, 2025)

Influence of selection bias in epidemiology research on extreme temperature and birth outcomes: evidence from a prospective birth cohort in China - Jie Ni; Zhenghong Zhu; Jiajun Luo; Dan Long; Yuyuan Bu; Yuye Jiang; Wei Wu; Miaochan Zhu; Xiaoxin Zhang; Cunrui Huang; Qing Wang; Qiong Wang (Environmental Research, 2025)

Signal molecule-mediated algae-bacteria interactions and membrane-enabled separation synergize wastewater bioremediation - Kai-Yuan Li; Jin-Long Zhou; Ashiwin Vadiveloo; Jia-Nan Li; Dan Zhou; Jia-Ming Wang; Ci Zhang; Yi-Lin Xie; Dong-Zhi Chen; Feng Gao (Chemical Engineering Journal, 2025)

Synergistic regulatory mechanisms of plant hormone combinations on the growth and lipid accumulation of Chlorella pyrenoidosa in saline wastewater - Qiao-Ling Zhao; Kai-Yuan Li; Jia-Qi Xi; Jin-Long Zhou; Dan-Ni Miao; Zeng-Ling Ma; Ying Zhang; Hai-Jun Luo; Feng Gao (Journal of Environmental Chemical Engineering, 2025)

Grass carp reovirus VP6 inhibits IFN production by degrading TBK1 through the autophagy pathway - Xiao Xu; Zhuo-Cong Li; Bao-Jie Cui; Can Zhang; Na Xu; Yang-Yang Wang; Dan-Dan Chen; Long-Feng Lu; Shun Li (Fish & Shellfish Immunology, 2025)

Phytochemical characterization, antioxidant, enzyme inhibitory and anti-inflammatory activities of Hedychium coccineum Buch.-Ham. ex Sm. rhizome - Yuanquan Ran; Dan Xie; Dan Long; Lu Jin; Guo Chen; Bing Yang; Dongxin Tang; Minyi Tian (Biochemical Systematics and Ecology, 2025)

Belowground biomass accumulation in a subtropical anthropogenic archipelago - Yunfan Hu; Tianxiang Li; Xuying Ye; Yuping Zhong; Bin Wang; Dan Long; Mengyuan Chen; Mengsi Zhou; Mingjian Yu; Jinliang Liu (Plant and Soil, 2025)

Torsade de Pointes and QT Prolongation Among Antifungal Triazoles: A Real-World, Retrospective, Observational, Pharmacovigilance Analysis of the FDA Adverse Event Reporting System (FAERS) Database - Long Chen; Ming-Jia Liu; Song Wang; Dan Yang; Nan-Nan Ding; Ji Zhang (Cardiovascular Toxicology, 2025)

An evolutionary game analysis of the promotion of shipborne low-temperature freezing technology for sea-caught shrimps among the government, fishermen, and consumers - Long Xu; Xiaojun Zhang; Haixia Yu; Peng Zhou; Dan Xu; Peipei Li; Xiaxia Chen (Frontiers in Marine Science, 2025)
In the era of heightened focus on sustainable marine fisheries development, the Shipborne Low-Temperature Freezing Technology is crucial for enhancing the preservation effect of seafood, improving transportation efficiency, and reducing energy consumption. It plays a key role in the sustainable development of the fishery industry. This paper constructs a tripartite evolutionary game model involving fishermen, consumers, and the government by using evolutionary game theory, and analyzes the interaction mechanism of the behaviors of the three parties. Based on field survey data, through model derivation and simulation, with results as follows: (1) Government subsidies positively influence choices at both the production and consumption ends. They incentivize fishermen to adopt Shipborne Low-Temperature Freezing Technology for storing wild-caught shrimp products, while also encouraging consumers to purchase shrimp products preserved through this technology. (2) Government subsidy structures have complex effects on the strategic choices of both fishermen and consumers. Expanding subsidies to fishermen positively impacts the adoption of Shipborne Low-Temperature Freezing Technology. (3) An appropriate online sales ratio can generate positive cross-channel effects, enabling the game system to reach an optimal equilibrium. In this state: Fishermen spontaneously adopt Shipborne Low-Temperature Freezing Technology; Consumers voluntarily purchase wild-caught shrimp preserved with Shipborne Low-Temperature Freezing Technology; The government withdraws subsidies for both fishermen and consumers.

New perspective on mechanism of L-arginine in promoting skeletal muscle growth of grass carp (Ctenopharyngodon Idella): Via enhancing skeletal muscle functions and regulating energy metabolism - Qiu-Yan Chen; Yu-Long Ma; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Xiao-Wan Jin; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Long-term simulation of process and hydrogeochemistry of gas field produced water reinjection into a limestone reservoir - Bo Liu; Weifeng Jing; Daixi Long; Jiahong Li; Dan Ding; Kunpeng Cai (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Rnai-mediated knockdown of nuclear receptors impairs cuticle formation by disrupting chitin metabolic pathway in Holotrichia oblita - Zhi-long Niu; Jian Wei; Qian Wang; Yu-bo Yang; Ying-Nan Gao; Lu Li; Jia Jia; Wei Guo; Dan Zhao (Journal of Insect Physiology, 2025)

Cyprinid herpesvirus 2 (CyHV-2) ORF67 inhibits IFN expression by competitively obstructing STING phosphorylation - Bao-Jie Cui; Can Zhang; Chu-Jing Zhou; Zhuo-Cong Li; Xiao Xu; Yang-Yang Wang; Dan-Dan Chen; Li Zhou; Long-Feng Lu; Shun Li (Fish & Shellfish Immunology, 2025)

Droplet-piezoelectric nanogenerators for simultaneous harvesting of droplet electrostatic and mechanical energy - Chunyan Li; Wenlong Pang; Zhiguang Li; Chaoyu Chen; Zhu Long; Lei Dai; Pengxiang Si; Yun Wu; Dan Zhang (Chemical Engineering Journal, 2025)

TET2 promotes UVB-induced cell death by activating RIPK3-MLKL-necroptosis signaling - Daijing Long; Yangfan Xu; Xuemei Li; Yilan Zeng; Ziting Tang; Lulu Liu; Yuanhong Liu; Xiule Zong; Shengbo Yang; Dan Wang (Chemico-Biological Interactions, 2025)

NPK-N application limits grain cadmium concentration of wheat via promoting Cd export during grain filling - Yiran Cheng; Yuanjiang He; Jia Chen; Weiping Li; Wenhui Xiang; Xing Chen; Dan Long; Jian Zeng; Yang Liu; Dongwei Wang; Dandan Wu; Lina Sha; et al. (Plant and Soil, 2025)

Bi-stage learning differential evolution for multimodal optimization problems - Chang-Long Wang; Zi-Jia Wang; Yi-Biao Huang; Dan-Ting Duan; Zhi-Hui Zhan; Sam Kwong; Jun Zhang (Swarm and Evolutionary Computation, 2025)

Identifying hydrogeochemistry evolution mechanism in high-sulfur non-ferrous metal mining areas via hydrochemical characteristics and isotopic evidence - Bing Wang; Lei Ma; Jia-zhong Qian; Yun-hai Fang; Wei Xie; Dan Ding; Huan Zhou; Yang Long; Han-ying Shen; Qiang Yang (Journal of Contaminant Hydrology, 2025)

Integrating spatiotemporal behavior, indoor-outdoor penetration, and ventilation rates to assess prenatal PM2.5 exposure and the association with birth weight - Dan Long; Xin Chen; Maimaitiminjiang Wulayin; Miaochan Zhu; Huailin Wang; Junwei Wu; Jianyong Lu; Liecheng Hong; Qing Wang; Zhenghong Zhu; Xiaoxin Zhang; Cunrui Huang; et al. (Atmospheric Pollution Research, 2025)

Utilization of UV/VUV irradiation for removal of human body fluids related pollutants in swimming pool water - Dan Li; Liangchen Long; Wei Xia; Weixin Zhao; Likui Feng; Xinhui Xia; Shufei He; Yu Liu; Shijie You; Liangliang Wei (Journal of Hazardous Materials, 2025)

Resource utilization of the waste lithium slag in oil-well cement under high temperature: Mechanical property, hydration behavior and environmental effect - Zhao Feng; Zeng Xueling; Long Dan; Gu Anlin; Mei Kaiyuan; Zhang Chunmei; Cheng Xiaowei (Journal of Environmental Chemical Engineering, 2025)

Bangong-Nujiang Neo-Tethyan Ocean (Central Tibet): Geodynamics, Crustal Evolution, Metallogeny, and Linkages to the “Yanshan Movement” - Lu-Lu Hao; Wan-Long Hu; Qiang Wang; Andrew C. Kerr; Wei Dan; Xiu-Zheng Zhang; Zong-Yong Yang; Peng Sun (Earth-Science Reviews, 2025)

Kinetics and morphology study of hydrate formation from CO2-H2O emulsion in glass beads - Ming-Long Wang; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Dan Rao; Yu Liu; De-Jun Xuan; Bei Liu; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Battery-free antenna sticker for wireless sensing joint rotation - Pengxiang Si; Mingrui Liang; Jihua Zou; Yu Kuang; Juntao Zhang; Qingsha S. Cheng; Yiqian Kong; Yuxin Cai; Guozhi Huang; Yun Wu; Zhu Long; Boxin Zhao; et al. (Chemical Engineering Journal, 2025)

Mitochondrial Treatment Improves Cognitive Impairment Induced by Lipopolysaccharide in Mice - Qiu-Qing Yan; Tian-Long Liu; Ling-Ling Liu; Yan-Su Wei; Yuan-Dan Zhao; Chao Yu; Zhen-Guo Zhong; Jin-Lan Huang; Deng-Pan Wu (Molecular Neurobiology, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

Regulation of innate lymphoid cell by microbial metabolites - Hongji Tao; Jingjing Geng; Long Bai; Dan Su; Yu Zhao; Guifang Xu; Mingming Zhang (Journal of Molecular Medicine, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Construction of phenothiazine-decorated ZnO quantum dots with intelligent response to bacterial pH/amidase microenvironment for inducing bacterial ferroptosis-like death - Wu-Bin Shao; Rong-Shuang Luo; Yan-Wei Huang; Long Cheng; Dan Zeng; Xiang Zhou; Li-Wei Liu; Song Yang (Chemical Engineering Journal, 2025)

Mixed exposure to PFOA and PFOS induces oocyte apoptosis and subfertility in mice by activating the Hippo signaling pathway - Xiang-Zhu Yan; Jia Peng; Yu-Qing Liu; Ruo-Nan Fan; Xin-Yi Ni; Ling Gong; Dan-Ni Zhang; Xin Huang; Shu-Hua Tan; Hai-Long Wang (Reproductive Toxicology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Study on the early diagnostic value of nanopore sequencing in alveolar lavage fluid smear-negative pulmonary tuberculosis - Yangjing Ou; Dan Li; Xi Long; Huiyang He; Ling Qing; Yuqiu Tian; Jing Ren; Qing Zhou; Yingzheng Tan (Brazilian Journal of Microbiology, 2025)

Fe2+ inhibits spring viraemia of carp virus proliferation via ATG14-dependent autophagy - Zhuo-Cong Li; Can Zhang; Na Xu; Xiao Xu; Ke-Jia Han; Chu-Jing Zhou; Yang-Yang Wang; Bao-Jie Cui; Dan-Dan Chen; Long-Feng Lu; Shun Li (Aquaculture, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Design and preparation of non-porous amorphous PEI-based polymers and their adsorption properties for anionic dyes - Henglong Tang; Mingyue Qian; Zhu Long; Dan Zhang; Chang Sun (Journal of Hazardous Materials, 2025)

Impact of different continuous fertilizations on the antibiotic resistome associated with a subtropical triple-cropping system over one decade - Jin Zheng; Ya-Ying Li; Yu-Sheng Lu; Dan Wang; Chong Liu; Huan-Long Peng; Chao-Hong Shi; Kai-Zhi Xie; Kun Zhang; Li-Li Sun; Chang-Min Zhou; Wen-Jie Gu (Environmental Pollution, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

The PHD transcription factor ThPHD5 regulates antioxidant enzyme activity to increase salt tolerance in Tamarix hispida - Yao-Shuo Tan; Jing-Hang Li; Pei-Long Wang; Dan-Ni Wang; Bai-Chao Liu; Sonethavy Phetmany; Yong-Xi Li; Qing-Jun Xie; Cai-Qiu Gao (Plant Science, 2025)

A new approach to high conversion CO2 hydrate sequestration by CO2/water emulsion injection into marine sediments - Ming-Long Wang; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Liang-Liang Ren; Ming Wang; Dan Rao; Yong-Quan Liu; Yi-Bo Hao; Bei Liu; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2025)

Potential preservative mechanisms of cardiac rehabilitation pathways on endothelial function in coronary heart disease - Wen-Tao Sun; Jian-Yong Du; Jia Wang; Yi-Long Wang; Er-Dan Dong (Science China Life Sciences, 2025)

Quantitative trait loci mapping for agronomic and leaf chemistry traits using high density linkage map in flue-cured tobacco (Nicotiana tabacum L.) - Ke Zhang; Chunqiong Wang; Dan Chen; Xiaowei Zhang; Haowei Sun; Jie Long; Haiyan Li; Jieyun Cai; Dan Li; Jiwu Zhang; Jinchu Yang; Dexin Liu; et al. (Euphytica, 2025)

Unveiling Frequency-Specific Microstate Correlates of Anxiety and Depression Symptoms - Siyang Xue; Xinke Shen; Dan Zhang; Zhenhua Sang; Qiting Long; Sen Song; Jian Wu (Brain Topography, 2025)

Electron beam irradiation in collaboration with Bi-Fe MOFs for oxidation of bisphenol A and reduction of Cr(VI): Kinetics, DFT calculation and mechanism - Dan Liu; Junhui He; Ruirui Wang; Zhen Zhao; Zhen Dong; Qiburi Bao; Long Zhao; Miao Yang (Journal of Environmental Chemical Engineering, 2024)

Exposure to greenspaces sourced soils improves mice gut microbiota - Gang-Long Zhou; Yan Xie; Yi-Dan Zhang; Lu Wang; Yu-Ting Xie; Hui-Ling Qiu; Xiao-Qi Zhu; Jian-Cheng Jiang; Yan Yang; Mingdeng Xiang; Guang-Hui Dong; Yuanzhong Zhou; et al. (Environmental Pollution, 2024)

Maternal Serum Iodine Concentrations in Early Pregnancy Exhibited Well Diagnostic Ability for Thyroid Dysfunction, Inverse Associations with Gestational Weight Gain, and Birth Size: Longitudinal Analyses Based on Huizhou Mother-Infant Cohort - Zhao-min Liu; Huan-huan Long; Dan Li; Ai-ping Fang; Chao-gang Chen; Cheng Wang; Min-min Li; Yi Wu; Su-juan Zhang; Wen-jing Pan (Biological Trace Element Research, 2024)

Effect of alfalfa downy mildew (Peronospora aestivalis) infection on the growth and development of Therioaphis trifolii (Homoptera: Aphidiidae) - Lin-bo Xu; Liang-bin Yu; Fang-zheng Yue; Dan-yang Wang; Wen-long Li; Ba-teer Wulan; Yan-wei Cui (Crop Protection, 2024)

Rapid, sensitive, and non-destructive on-site quantitative detection of nanoplastics in aquatic environments using laser-backscattered fiber-embedded optofluidic chip - Yongkai Lu; Tianxiang Ji; Wenjuan Xu; Dan Chen; Ping Gui; Feng Long (Journal of Hazardous Materials, 2024)

Quantitative evaluation of hydrate-based CO2 storage in unsealed marine sediments: Viewpoint from the driving force of hydrate formation and CO2-water contact ability - Hong-Nan Chen; Yi-Fei Sun; Wei-Xin Pang; Ming-Long Wang; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Bo-Jian Cao; Dan Rao; Chang-Yu Sun; Guang-Jin Chen (Fuel, 2024)

Foliar application of silicon and selenium reduce the toxicity of cadmium to soybeans - Jie Chen; Dan Yang; Min Xu; Lulu Long; Qiao Li; Jiyuan Jin; Chao Chen; Jun Wu; Gang Yang (Chemosphere, 2024)

Will greenhouse gas emissions increase with mining depth in coal mines? An analysis of gas occurrence under varying in-situ stress conditions - Wei Zhao; Dan Zhao; Kai Wang; Long Fan; Zhihu Zhao; Huzi Dong; Longyong Shu (Science of The Total Environment, 2024)

High sulfur-to-iron ratios enhance thallium(I) sequestration by sulfidated zero-valent iron - Nana Wang; Fengli Liu; Huosheng Li; Ping Zhang; Juanxi Huang; Gaosheng Zhang; Tangfu Xiao; Jianyou Long; Dan Peng; Yuqi Wang; Huanbin Huang; Zengping Ning (Process Safety and Environmental Protection, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

Biomaterials in heterotopic ossification: Prophylaxis and promotion - Xu Lou; Dan Huang; Guangfeng Li; Long Bai; Jiacan Su; Hua Yue (Chemical Engineering Journal, 2024)

Real-time monitoring of maize phenology with the VI-RGS composite index using time-series UAV remote sensing images and meteorological data - Ziheng Feng; Zhida Cheng; Lipeng Ren; Bowei Liu; Chengjian Zhang; Dan Zhao; Heguang Sun; Haikuan Feng; Huiling Long; Bo Xu; Hao Yang; Xiaoyu Song; et al. (Computers and Electronics in Agriculture, 2024)

Co-incineration of medical waste in municipal solid waste incineration increased emission of chlorine/brominated organic pollutants - Congcong Zhang; Ziang Bai; Xingshuang Liu; Dan Xia; Xiang Li; Jisheng Long; Zhongtao Sun; Yaojian Li; Yifei Sun (Science of The Total Environment, 2024)

SIRT1-Mediated HMGB1 Deacetylation Suppresses Neutrophil Extracellular Traps Related to Blood–Brain Barrier Impairment After Cerebral Venous Thrombosis - Shuwen Mu; Ziqi Li; Long Lin; Di Wang; Fei Yang; Li Chen; Liang Xian; Kunzhe Lin; Yinghong Lin; Dan Ye; Yang Yang; Liangfeng Wei; et al. (Molecular Neurobiology, 2024)

Statistical and modeling analyses of urban impacts on winter precipitation - Jiahui Liu; Yue Xing; Dan Li; Long Yang; Guangheng Ni (Urban Climate, 2024)

Exploring the Impact of Biodegradable and Nonbiodegradable Microplastic Particles on Pb Absorption in Maize - Dan QIU; Chunmiao LU; Huarong SUN; Chaohang LI; Guangqiang LONG; Ping ZHAO; Yijun LONG; Yue DING; Cuixia SU; Zhengyan PAN; Yuefang CAO; Shuran HE (Journal of Soils and Sediments, 2024)

Effects of micro- and nano-plastics on growth, antioxidant system, DMS, and DMSP production in Emiliania huxleyi - Juan Yu; Ji-Yuan Tian; Yu Jiang; Xue-Dan Wang; Xin-Ran Song; Long-Fei Liu; Gui-Peng Yang (Environmental Pollution, 2024)

Effects of Mesenchymal Stem Cells-Derived Extracellular Vesicles on Inhibition of Hepatic Fibrosis by Delivering miR-200a - Ai-Lei Xu; Long Han; Jun Yan; Dan Liu; Wei Wang (Tissue Engineering and Regenerative Medicine, 2024)

Identification of lignans as ATP citrate lyase (ACLY) inhibitors from the roots of Pouzolzia zeylanica - Jin-Long Li; Jia-Yi Jiang; Shan-Shan Gu; Lei Zhang; Yan Sun; Xue-Han Wang; Dan-Yu Li; Zhe-Yu Chen; Sheng-Shi Jiang; Wei-Zhong Zhu; Hao-Wen Jiang; Hong-Jie Zhang (Natural Product Research, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Enhancing water quality and ecosystems of reclaimed water-replenished river: A case study of Dongsha River, Beijing, China - Xinlei Shi; Liping Wang; Ai Chen; Wenze Yu; Yongze Liu; Xueli Huang; Xiaoyan Long; Yuqi Du; Dan Qu (Science of The Total Environment, 2024)

The super-pangenome of Populus unveils genomic facets for its adaptation and diversification in widespread forest trees - Tingting Shi; Xinxin Zhang; Yukang Hou; Changfu Jia; Xuming Dan; Yulin Zhang; Yuanzhong Jiang; Qiang Lai; Jiajun Feng; Jianju Feng; Tao Ma; Jiali Wu; et al. (Molecular Plant, 2024)

CRISPR/Cas12a powered air-displacement enhanced evanescent wave fluorescence fiber-embedded microfluidic biochip for nucleic acid amplification-free detection of Escherichia coli O157:H7 - Xiangzhi Han; Dan Song; Wenjuan Xu; Laiya Lu; Anna Zhu; Feng Long (Journal of Hazardous Materials, 2024)

The impact of arbuscular mycorrhizal fungi and endophytic bacteria on peanuts under the combined pollution of cadmium and microplastics - Zi-tian Pu; Dan-dan Wang; Wei-xing Song; Chao Wang; Zhao-yu Li; Ying-long Chen; Tori Shimozono; Zhao-min Yang; Yong-qiang Tian; Zhi-hong Xie (Journal of Hazardous Materials, 2024)

Yield has minimal effect on whole-grain mineral density of modern soft wheat compared to production environment, genotype, and test weight - Curtis B. Adams; Ryan Graebner; Juliet Marshall; Clark Neely; Dan S. Long; Catherine L. Reardon; Christopher W. Rogers (Field Crops Research, 2024)

Uptake, translocation, and metabolism of organophosphate esters (OPEs) in plants and health perspective for human: A review - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yu-Fei Feng; Long-Wei Zhang; Xue-Yi Jiang; Yi-Shan Liu; Dong-Wei Wu; Jun-Jie Hu (Environmental Research, 2024)

Monospecific and ultrasensitive detection of ofloxacin: A computational chemistry-assisted hapten screening strategy and analysis of molecular recognition mechanism - Jiaxu Xiao; Liangni Qin; Dan Zhao; Niexie Huang; Wennuo Xu; Linwei Zhang; Xiaoming Pan; Shiyun Han; Mingyue Ding; Long Li; Tao Le; Dapeng Peng (Journal of Hazardous Materials, 2024)

Dialysis bag-microalgae photobioreactor: Novel strategy for enhanced bioresource production and wastewater purification - Jin-Long Zhou; Jia-Nan Li; Dan Zhou; Jia-Ming Wang; Yi-Hang Ye; Ci Zhang; Feng Gao (Journal of Environmental Management, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

The role of glutathione in stabilizing aromatic volatile organic compounds in Rougui Oolong tea: A comprehensive study from content to mechanisms - Yanqun Xu; Jieqiong Wang; Ziqing Wu; Jing Huang; Zhenbiao Li; Jiayi Xu; Dan Long; Tian Ye; Gennv Wang; Junfeng Yin; Zisheng Luo; Yongquan Xu (Food Chemistry, 2024)

Insight into the effect of cultivar and altitude on the identification of EnshiYulu tea grade in untargeted metabolomics analysis - Dan Zou; Xiao-Li Yin; Hui-Wen Gu; Zhi-Xin Peng; Baomiao Ding; Zhenshun Li; Xian-Chun Hu; Wanjun Long; Haiyan Fu; Yuanbin She (Food Chemistry, 2024)

A versatile SERS platform based on conductive MOF-enforced carbon paper for rapidly and sensitively monitoring diazepam in aquatic products - Chengke Zhu; Chaoying Ren; Wenshan Jiang; Dan Liu; Yiyang Huang; Wenjie Wang; Kuan Chang; Long Zhu; Qinzhi Wang (Food Chemistry, 2024)

Ecological impact of surfactant Tween-80 on plankton: High-scale analyses reveal deeper hazards - Duanyang Yuan; Yaoyue Long; Dan Liu; Fangjie Zhou; Change Liu; Liqiang Chen; Ying Pan (Science of The Total Environment, 2024)

Piezoelectric BaTiO3 nanoparticles as oxidase mimics breaking pH limitation for colorimetric detection of glutathione reductase - Jijun Liu; Dan Yang; Weiling Hu; Na Huang; Yu Rong; Yijuan Long; Huzhi Zheng (Chemical Engineering Journal, 2024)

Recent advance in high-intensity ultrasound modification of blue food protein: Mechanisms, functional properties and structural alterations - Zhihui Yu; Yating Gao; Xinyi Jia; Shuai Cui; Li Ma; Dan Zheng; Xin Li; Long Li; Lixin Zhang; Yisheng Chen (Trends in Food Science & Technology, 2024)

Whole-body aging mediates the association between exposure to volatile organic compounds and osteoarthritis among U.S. middle-to-old-aged adults - Hao-long Zhou; Dong-sheng Di; Zhang-bo Cui; Ting-ting Zhou; Ting-ting Yuan; Qian Liu; Jian-li Zhang; Xiao Luo; Dan-yang Ling; Qi Wang (Science of The Total Environment, 2024)

Uptake mechanism, translocation, and transformation of organophosphate esters in water hyacinth (Eichhornia crassipes): A hydroponic study - Zhi-Lang Lao; Dan Wu; Hui-Ru Li; Yi-Shan Liu; Long-Wei Zhang; Yu-Fei Feng; Xue-Yi Jiang; Dong-Wei Wu; Jun-Jie Hu; Guang-Guo Ying (Environmental Pollution, 2024)

Inorganic salt-assisted hydrothermal synthesis of composite vanadium oxides for stabilization of aqueous zinc ion batteries with low current density cycling - Peng Luo; Dan Li; Junyao Long; Shiyao Nie; Xiaolan Chen; Zhaohui Li; Gangtie Lei (Chemical Engineering Journal, 2024)

Antiepileptic drugs in aquatic environments: Occurrence, toxicity, transformation mechanisms and fate - Quanzhen Liu; Long Wang; Xiong Xu; Saihong Yan; Jinmiao Zha; Donghong Wang; Dan Zhu (Critical Reviews in Environmental Science and Technology, 2023)

Investigation of filtration performance and phosphorus removal in an electric field controlled dynamic membrane bioreactor - Long Chen; Miao Lv; Yang-Cheng Ding; Zi-Ang Lv; Dan-Na Ding; Di Wu; Haiping Yuan; Nanwen Zhu; Hua-Jun Feng (Chemical Engineering Journal, 2023)

Spontaneous compartmentalization in chitosan - phytate - lignosulfonate microparticles by gas-shearing microfluidics - Qingli Qu; Long Chen; Weixia Cheng; Jules Muhire; Anquan Yang; Jing Wang; Min Xie; Xiaoli Zhang; Dan Huang; Ranhua Xiong; Dong Pei; Chaobo Huang (Chemical Engineering Journal, 2023)

Ubiquitin ligase enzymes and de-ubiquitinating enzymes regulate innate immunity in the TLR, NLR, RLR, and cGAS-STING pathways - Wang Jiang; Mengling Li; Siyuan Peng; Tian Hu; Yan Long; Jiayi Zhang; Dan Peng; Yueming Shen (Immunologic Research, 2023)

Revealing the chemical differences and their application in the storage year prediction of Qingzhuan tea by SWATH-MS based metabolomics analysis - Zhi-Quan Li; Xiao-Li Yin; Hui-Wen Gu; Dan Zou; Baomiao Ding; Zhenshun Li; Ying Chen; Wanjun Long; Haiyan Fu; Yuanbin She (Food Research International, 2023)

Optimizing mechanical stretchability and photovoltaic performance in all-polymer solar cells from a two-donor polymer blend - Mingfei Li; Kaihu Xian; Wenchao Zhao; Dan Sheng; Chunhui Liu; Xin Li; Weiwei Li; Long Ye (Chemical Engineering Journal, 2023)

Expression of aldose reductase in mouse endometrial epithelial cells and its role in sperm capacitation - Yi Lei; Li Nie; Yun Long; Dan Zhao; Min Liu; Yi-cheng Wang; Xue-qin Zhang; Miao-miao Xu; Huan Liu; Jin-hu Zhang; Dong-zhi Yuan; Li-min Yue (Theriogenology, 2023)

Corrigendum to “Ca2+ plays an antiviral role by increasing p53 expression to achieve protection against spring viraemia of carp virus infection” [Fish Shellfish Immunol. 102 (2020) 449–459/455] - Long-Feng Lu; Xiao-Yu Zhou; Can Zhang; Zhuo-Cong Li; Dan-Dan Chen; Yong-An Zhang; Shun Li (Fish & Shellfish Immunology, 2023)

Omega-3 Polyunsaturated Fatty Acids Protect Neurological Function After Traumatic Brain Injury by Suppressing Microglial Transformation to the Proinflammatory Phenotype and Activating Exosomal NGF/TrkA Signaling - Long Lin; Shaorui Zheng; Jinqing Lai; Dan Ye; Qiaomei Huang; Zhe Wu; Xiangrong Chen; Shousen Wang (Molecular Neurobiology, 2023)

Smartphone-assisted colorimetric and near-infrared ratiometric fluorescent sensor for on-spot detection of H2O2 in food samples - Xiaodong Chen; Dan He; Jiaye Shentu; Sanxiu Yang; Yunfei Yang; Yuqing Wang; Rumeng Zhang; Kun Wang; Jing Qian; Lingliang Long (Chemical Engineering Journal, 2023)

Freshly formed elemental sulfur-sulfidated zero-valent manganese for enhanced chromium(VI) removal from wastewater - Jianyou Long; Yijie Zheng; Shuxiang Zha; Juanxi Huang; Dan Peng; Gaosheng Zhang; Tangfu Xiao; Yuxian Liu; Guoliang Yang; Huosheng Li (Chemical Engineering Journal, 2023)

A facile strategy to fabricate high-barrier, water- and oil-repellent paper with carboxymethyl cellulose/collagen fiber/modified polyvinyl alcohol - Ruifeng Zhu; Wenzhi Lv; Chang Sun; Chengrong Qin; Dan Zhang; Zhu Long (Carbohydrate Polymers, 2023)

Time frequency domain combined deconvolution method - Wei Zhou; Huailai Zhou; Dan Long; Haitao Yan; Junping Liu (Acta Geophysica, 2023)

Bio-aerogels derived from corn stalk and Premna Microphylla leaves as eco-friendly sorbents for oily water treatment: The role of microstructure in adsorption performance - Rongchuan Ye; Huosheng Li; Jianyou Long; Yaxuan Wang; Dan Peng (Journal of Cleaner Production, 2023)

Rooftop solar policies feasibility assessment model: Vietnam case study - Shahab Qureshi; Long Phan-Van; Linh Dan Nguyen; Tuyen Nguyen-Duc (Energy Policy, 2023)

Preparation, characterization and safety evaluation of Ligusticum chuanxiong essential oils liposomes for treatment of cerebral ischemia-reperfusion injury - Yu Long; Shuang Yu; Dan Li; Ai Shi; Yin Ma; Jie Deng; Xiao-qiu Li; Jing Wen; Yuan-yuan Wu; Yue Hu; Xiao-fang He; Nan Li; et al. (Food and Chemical Toxicology, 2023)

Quantitative Assessment of Climate Change Impacts on Forest Ecosystems - Dan Liu; Hao Yan; Cheng Long Yu; Shi Ping Yin; Cheng Wei Wang; Li Juan Gong (Forest Science, 2023)
Characterizing and predicting the response of terrestrial ecosystems to global change is part of the fundamental challenges of contemporary ecology and ecological conservation. The assessment of climate change impact on forest ecosystems has rarely used a multi-index fusion method for quantitative evaluation. We used forest distribution, net primary productivity, and vegetation coverage to establish an assessment model of the impact of climate change on forest ecosystems. We analyzed the change characteristics of these indicators in the Heilongjiang Province of China. Our results indicate the following: (1) from 2001 to 2019, the forest area in Heilongjiang Province ranged from 234,000 to 246,000 km2. The forest net primary productivity (NPP) ranged from 4.40 to 5.55 MgC·ha-1·yr-1, and the vegetation coverage ranged from 42.42% to 67.64%. The forest NPP and the vegetation coverage showed a significant upward trend. (2) The values of forest ecological roles were significantly positively correlated with the climatic potential. (3) The contribution rate of climate change to forest ecosystem change was negatively correlated with forest coverage, which varied from 4.79% to 18.07% in different regions (cities) of the province. Study Implications: Assessing the influence of climate on forest ecosystems comprehensively and accurately before the government prepares ecological measures is necessary. However, the responses of vegetation coverage and net primary productivity to climate change may not be consistent, so climate studies that consider forest ecosystem change trends by a single indicator may have confounding results. We established a model for evaluating the impact of climate change on forest ecosystems to solve this problem. This knowledge may provide a reference for the response, adaptation, and vulnerability assessment of forest ecosystems to climate change.

Optimization of natural deep eutectic solvents extraction of flavonoids from Xanthoceras sorbifolia Bunge by response surface methodology - Zhi-ao Feng; Dan Yang; Jin-jin Guo; Yu-kun Bo; Long-shan Zhao; Ming An (Sustainable Chemistry and Pharmacy, 2023)

Effects of polyethylene and biodegradable microplastics on photosynthesis, antioxidant defense systems, and arsenic accumulation in maize (Zea mays L.) seedlings grown in arsenic-contaminated soils - Huarong Sun; Yilan Shi; Ping Zhao; Guangqiang Long; Chaohang Li; Jiajing Wang; Dan Qiu; Chunmiao Lu; Yue Ding; Lin Liu; Shuran He (Science of The Total Environment, 2023)

Manganese and copper additions differently reduced cadmium uptake and accumulation in dwarf Polish wheat (Triticum polonicum L.) - Xing Chen; Shan Yang; Jian Ma; Yiwen Huang; Yi Wang; Jian Zeng; Jun Li; Siyu Li; Dan Long; Xue Xiao; Lina Sha; Dandan Wu; et al. (Journal of Hazardous Materials, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

A ratiometric fluorescent biosensing platform for ultrasensitive detection of Salmonella typhimurium via CRISPR/Cas12a and silver nanoclusters - Long Ma; Jiajing Wang; Yaru Li; Dan Liao; Wenlu Zhang; Xiao Han; Shuli Man (Journal of Hazardous Materials, 2023)

Markedly boosted peroxymonosulfate- and periodate-based Fenton-like activities of iron clusters on sulfur/nitrogen codoped carbon: Key roles of a sulfur dopant and compared activation mechanisms - Yangke Long; Shixin Huang; Jianlin Sun; Dan Peng; Zuotai Zhang (Science of The Total Environment, 2023)

A spectral learning path for simultaneous multi-parameter detection of water quality - Zhiqiang Guo; Fenli Liu; Qiannan Duan; Wenjing Wang; Qianru Wan; Yicai Huang; Yuting Zhao; Lu Liu; Yunjin Feng; Libo Xian; Hang Gao; Yiwen Long; et al. (Environmental Research, 2023)

FeCl3 and Fe2(SO4)3 differentially reduce Cd uptake and accumulation in Polish wheat (Triticum polonicum L.) seedlings by exporting Cd from roots and limiting Cd binding in the root cell walls - Qin Yao; Weiping Li; Ying Liu; Yiran Cheng; Xue Xiao; Dan Long; Jian Zeng; Dandan Wu; Lina Sha; Xing Fan; Houyang Kang; Haiqin Zhang; et al. (Environmental Pollution, 2023)

Nonoxidative propane dehydrogenation by isolated Co2+ in BEA zeolite: Dealumination-determined key steps of propane C H activation and propylene desorption - Sheng Wei; Hua Dai; Jiangping Long; Hongqiao Lin; Junkun Gu; Xupeng Zong; Dan Yang; Yu Tang; Yanhui Yang; Yihu Dai (Chemical Engineering Journal, 2023)

Dynamic mechanical characteristics of frozen subgrade soil subjected to freeze-thaw cycles - Dan Wang; En-long Liu; Cheng-song Yang; You-qian Liu; Sheng-xian Zhu; Qi-hao Yu (Journal of Mountain Science, 2023)

Recent Development of Algal Biochar for Contaminant Remediation and Energy Application: A State-of-the Art Review - Thanh-Binh Nguyen; Van-Truc Nguyen; Hong-Giang Hoang; Ngoc-Dan-Thanh Cao; Thanh-Tin Nguyen; Thi-Dieu-Hien Vo; Ngoc-Kim-Qui Nguyen; Mai-Duy-Thong Pham; Duc-Long Nghiem; Thi-Kim-Quyen Vo; Cheng-Di Dong; Xuan-Thanh Bui (Current Pollution Reports, 2022)

A Fundamental Role of Slope Aspect and Elevation in Controlling Diversity Patterns of Soil Bacterial Communities: Insights from an Arid-Montane Ecosystem in China - Long-Fei Chen; Jun-Qia Kong; Zhi-Bin He; Wen-Zhi Zhao; Ming-Dan Song; Yue-Mei Li; Yuan Gao; Shu-Ping Yang (Journal of Soil Science and Plant Nutrition, 2022)

STING/NF-κB/IL-6-Mediated Inflammation in Microglia Contributes to Spared Nerve Injury (SNI)-Induced Pain Initiation - Jia Sun; Ya-qun Zhou; Bing-yang Xu; Jia-yan Li; Long-qing Zhang; Dan-yang Li; Shuang Zhang; Jia-yi Wu; Shao-jie Gao; Da-wei Ye; Wei Mei (Journal of Neuroimmune Pharmacology, 2022)

Differential Study of Microbiota in the Gill and Intestine of Silver Carp (Hypophthalmichthys molitrix) from the Algae-Dominated and Hydrophyte-Dominated Areas of Taihu Lake, China - Dan Zhou; Ting Zhang; Long Ren; Di-An Fang; Dong-Po Xu (Fishes, 2022)
Both fish gills and guts can support lots of microbiota that play important roles in the health and growth of hosts. Although the microbiota of silver carp has been widely studied, the data on microbial variation according to fish tissues and local habitats are lacking. In this study, the microbes in the guts and gills of silver carp (Hypophthalmichthys molitrix) from the hydrophyte-dominated region (zone H) and the algae-dominated region (zone A) of Taihu Lake in autumn were analyzed. Proteobacteria, Cyanobacteria, and Firmicutes were the dominant bacteria in silver carp. The microbial diversity was higher in the gills than that in the intestines, and higher in fish from zone H than that from zone A. Beta diversity analysis revealed significant differences in microbial community structures between gill and guts, and between fish from the two habitats. Gills had a higher abundance of phyla Actinobacteria, Bacteroidetes, and Deinococcus-Thermus, and a lower abundance of verrucomicrobia than the intestine. Both tissues possessed indicator taxa, while many indicator taxa in the gill were conditional pathogens. Compared to fish from zone H, fish from zone A had more abundant Cyanobacteria, and less abundant Proteobacteria and Bacteroidetes. PICRUSt2 analysis revealed that fish microbial functions were mainly associated with metabolism, replication, repair, folding, sorting, and degradation. These results showed that the microbial community of silver carp from Taihu Lake varied according to tissues and habitats.

Fine mapping of the reduced height gene Rht22 in tetraploid wheat landrace Jianyangailanmai (Triticum turgidum L.) - Chao Wang; Yunjing Bao; Qin Yao; Dan Long; Xue Xiao; Xing Fan; Houyang Kang; Jian Zeng; Lina Sha; Haiqin Zhang; Dandan Wu; Yonghong Zhou; et al. (Theoretical and Applied Genetics, 2022)

Identification and QTL mapping of important agronomic traits based on rice short-wide grain CSSL-Z752 with restorer line Xihui 18 as background - Lin-Jun Cai; Han Yun; Xiao-Long Zhong; Dan Du; Xi-Man Peng; Ji-Chao Dai; Zhen-Lin Yang; Fang-Ming Zhao; Chang-Wei Zhang (Cereal Research Communications, 2022)

Integrated Analyses of miRNome and Transcriptome Reveal the Critical Role of miRNAs Toward Heat Stress Response in Isochrysis galbana - Jia-Yi Cao; Si-Min Xu; Ying-Ying Wang; Xie-Dan Long; Shuo-Nan Ma; Cheng-Xu Zhou; Ji-Lin Xu; Xiao-Jun Yan (Marine Biotechnology, 2022)

Two new 2,5-diketopiperazine derivatives from mangrove-derived endophytic fungus Nigrospora camelliae-sinensis S30 - Dan-Yu Huang; Xu-Hua Nong; Yu-Qin Zhang; Wei Xu; Long-Yu Sun; Tao Zhang; Guang-Ying Chen; Chang-Ri Han (Natural Product Research, 2022)

Stability evaluation for steep bank slope with microseismic monitoring in Three Gorges Reservoir area - Qing-ming Xie; Kui Long; Zi-mu Li; Li-chuan Chen; Hong Liu; Hong Xu; Fei He; Dan Liang; Xue-kun Xiang; Qiang Ma (Journal of Mountain Science, 2022)

Characterization, expression, and function analysis of AKR1A1 gene from yellow catfish (Tachysurus fulvidraco) - Long Yang; Shuting Zheng; Dan Kong; Shenghan Xiang; Jianfen Wu; Neng Wan; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2022)

Economic and management value of weed maps at harvest in semi-arid cropping systems of the US Pacific Northwest - Judit Barroso; Carolina San Martin; John D. McCallum; Dan S. Long (Precision Agriculture, 2021)

Investigations of solid culture–induced acquisition of desiccation tolerance in liquid suspension culture of Nostoc flagelliforme - Xiao-Long Yuan; Xiang Gao; Wen Liu; Yang She; Tao Zheng; Hui-Dan Xue (Journal of Applied Phycology, 2021)

Assessment of probiotic adhesion and inhibitory effect on Escherichia coli and Salmonella adhesion - Ya Wang; Dan Jia; Jia-hui Wang; He-hai Li; Jun-long Liu; Ai-hong Liu; Jin-ming Wang; Gui-quan Guan; Jian-xun Luo; Hong Yin; You-quan Li (Archives of Microbiology, 2021)

Correction to: HOXA11‑AS promotes the migration and invasion of hepatocellular carcinoma cells by inhibiting miR‑124 expression by binding to EZH2 - Wen‑long Zhang; Ya‑nan Zhao; Zhang‑zhen Shi; Gui‑ying Gu; Dan Cong; Chen Wei; Yuan‑song Bai (Human Cell, 2021)

Geniposide-Loaded Liposomes for Brain Targeting: Development, Evaluation, and In Vivo Studies - Jinyan Wan; Yu Long; Songyu Liu; Yulu Zhang; Yan Xiang; Dan Li; Ai Shi; Yu Shuang; Ying Li; Yanan He; Nan Li; Yongmei Guan (AAPS PharmSciTech, 2021)

Contributions of natural climate variability on the trends of seasonal precipitation extremes over China - Fuqiang Cao; Tao Gao; Li Dan; Fengxia Zhao; Xiang Gong; Xinyu Zhang; Xiaoyu Long; Junjie Zhan (International Journal of Climatology, 2021)
The increased trends of extreme precipitation events over China have been partially attributed to global warming, while it is unclear how the natural climate variability affect these variations in extreme rainfall trends. Here we examine the contributions of large‐scale modes climate variability from the Pacific Ocean, which are represented by El Niño‐Southern Oscillation (ENSO) and Pacific Decadal Oscillation (PDO), on the trends of seasonal extreme events across China. Results show that the effects of climate variability modes on precipitation extremes exhibit evidently spatiotemporal characteristics at the seasonal scale. A significant positive trend is found over southeastern and northwestern China in four seasons, and substantial increases in two types of extreme events are also seen over northwestern China in spring and winter. Most of the seasonal trends of extreme precipitation events can be explained by the trends of the principal components. El Niño (La Niña) and PDO–like sea surface temperature (SST) anomalies over the Pacific have a close linkage with the variations in precipitation extremes. By modulating the large‐scale atmospheric circulations, these Pacific SST anomalies associated with climatic oscillations, such as ENSO and PDO, provide the conducive conditions responsible for the occurrences of seasonal precipitation extremes across China. The seasonal trends of extreme events can be largely explained by the variability of the ENSO and PDO episodes, with a relatively larger modulation of PDO as compared to ENSO. These researches have important implications for improving seasonal flood disaster predictability and climate model performances.

Relationships between soil respiration and hyperspectral vegetation indexes and crop characteristics under different warming and straw application modes - Sicheng Ding; Xuewen Yao; Jin Wang; Ximing Deng; Miaomiao Zhang; Jilan Long; Shutao Chen; Zhenghua Hu; Dan Wang; Yanling Wang; Jun Wang; Tingting Zhang (Environmental Science and Pollution Research, 2021)

Carbon storage of the forest and its spatial pattern in Tibet, China - Long-yu Jia; Gen-xu Wang; Ji Luo; Fei Ran; Wei Li; Jun Zhou; Dan-li Yang; Wen-bo Shi; Qian Xu; Kun Zhu; Yang Yang (Journal of Mountain Science, 2021)

Residue management changes soil phosphorus availability in a long-term wheat-fallow rotation in the Pacific Northwest - Zhengjuan Yan; Harold Collins; Stephen Machado; Dan Long (Nutrient Cycling in Agroecosystems, 2021)

Spatial variation and fractionation of fluoride in tobacco-planted soils and leaf fluoride concentration in tobacco in Bijie City, Southwest China - Mei Wang; Long Zhang; Yanxiang Liu; Dan Chen; Lei Liu; Caibing Li; Kyong Ju Kang; Lingyu Wang; Zhenli He; Xiaoe Yang (Environmental Science and Pollution Research, 2021)

Cloning and expression of AGL19 gene in two Lonicera macranthoides varieties - YU QING LONG; XIA LIU; JUAN ZENG; CAN LI; XIANG DAN LIU; RI BAO ZHOU (Journal of Genetics, 2021)

Application of different foliar iron fertilizers for enhancing the growth and antioxidant capacity of rice and minimizing cadmium accumulation - Xinqi Wang; Sihan Deng; Yimin Zhou; Jiumei Long; Dan Ding; HuiHui Du; Ming Lei; Congying Chen; Bai Qing Tie (Environmental Science and Pollution Research, 2021)

Correction to: A20 prevents obesity-induced development of cardiac dysfunction - Wenjing Xu; Cheng Wang; Minglu Liang; Long Chen; Qin Fu; Fengxiao Zhang; Yan Wang; Dan Huang; Kai Huang (Journal of Molecular Medicine, 2021)

Adakitic rocks at convergent plate boundaries: Compositions and petrogenesis - Qiang Wang; Lulu Hao; Xiuzheng Zhang; Jinsheng Zhou; Jun Wang; Qiwei Li; Lin Ma; Long Zhang; Yue Qi; Gongjian Tang; Wei Dan; Jingjing Fan (Science China Earth Sciences, 2020)

Fine-Grained Topography and Modularity of the Macaque Frontal Pole Cortex Revealed by Anatomical Connectivity Profiles - Bin He; Long Cao; Xiaoluan Xia; Baogui Zhang; Dan Zhang; Bo You; Lingzhong Fan; Tianzi Jiang (Neuroscience Bulletin, 2020)
The frontal pole cortex (FPC) plays key roles in various higher-order functions and is highly developed in non-human primates. An essential missing piece of information is the detailed anatomical connections for finer parcellation of the macaque FPC than provided by the previous tracer results. This is important for understanding the functional architecture of the cerebral cortex. Here, combining cross-validation and principal component analysis, we formed a tractography-based parcellation scheme that applied a machine learning algorithm to divide the macaque FPC (2 males and 6 females) into eight subareas using high-resolution diffusion magnetic resonance imaging with the 9.4T Bruker system, and then revealed their subregional connections. Furthermore, we applied improved hierarchical clustering to the obtained parcels to probe the modular structure of the subregions, and found that the dorsolateral FPC, which contains an extension to the medial FPC, was mainly connected to regions of the default-mode network. The ventral FPC was mainly involved in the social-interaction network and the dorsal FPC in the metacognitive network. These results enhance our understanding of the anatomy and circuitry of the macaque brain, and contribute to FPC-related clinical research.

Heme oxygenase 1 plays a crucial role in swamp eel response to oxidative stress induced by cadmium exposure or Aeromonas hydrophila infection - Yuwei Zang; Shuting Zheng; Fang Tang; Long Yang; Xiping Wei; Dan Kong; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2020)

Catalytic performance promoted on Pt-based diesel oxidation catalyst assisted by polyvinyl alcohol - Yanli Liang; Xinmei Ding; Jianli Wang; Ming Zhao; Yi Dan; Long Jiang; Yaoqiang Chen (Environmental Science and Pollution Research, 2020)

Effect of dietary isoleucine on skin mucus barrier and epithelial physical barrier functions of hybrid bagrid catfish Pelteobagrus vachelli × Leiocassis longirostris - Long Yin; Ye Zhao; Xiao-Qiu Zhou; Chao Yang; Lin Feng; Yang Liu; Wei-Dan Jiang; Pei Wu; Jian Zhou; Juan Zhao; Jun Jiang (Fish Physiology and Biochemistry, 2020)

2(5H)-Furanone Disrupts Bacterial Biofilm Formation and Indirectly Reduces the Settlement of Plantigrades of the Mussel Mytilus coruscus - Yi-Feng Li; Xin Zhu; Zhi-Yang Cheng; Xiao Liang; You-Ting Zhu; Dan-Dan Feng; Sergey Dobretsov; Jin-Long Yang (Frontiers in Marine Science, 2020)

Developing effective management solutions for controlling stinking passionflower (Passiflora foetida) and promoting the recovery of native biodiversity in Northern Australia - Tommaso Jucker; Vicki Long; David Pozzari; Dan Pedersen; Ben Fitzpatrick; Paul B. Yeoh; Bruce L. Webber (Biological Invasions, 2020)

Characterization of an aerobic denitrifier Enterobacter cloacae strain HNR and its nitrate reductase gene - Bin Zhao; Qiao Dan; Long Jie Guo; Qiang An; Jin Song Guo (Archives of Microbiology, 2020)

Efficacy of amisulpride on postoperative nausea and vomiting: a systematic review and meta-analysis - Lu-Feng Zhang; Chao-Fan Zhang; Wen-Xin Tang; Long He; Yang Liu; Dan-Dan Tian; Yan-Qiu Ai (European Journal of Clinical Pharmacology, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Transcriptome analysis of axillary bud differentiation in a new dual-axillary bud genotype of sugarcane - Dan Chen; Xin Lu; Xiaoyang Wu; Xiongmei Ying; Wenjie Long; Huosheng Su; Hongbo Liu; Xiuqin Lin; Chaohua Xu; Qing Cai (Genetic Resources and Crop Evolution, 2020)

Molecular characterization of a novel botoulivirus from the phytopathogenic fungus Sclerotinia minor - Na Liang; Dan Yang; Mingde Wu; Jing Zhang; Guoqing Li; Long Yang (Archives of Virology, 2020)

Microbial methane production is affected by secondary metabolites in the heartwood of living trees in upland forests - Huan-Long Li; Xi-Mei Zhang; Feng-Dan Deng; Xing-Guo Han; Chun-Wang Xiao; Shi-Jie Han; Zhi-Ping Wang (Trees, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

HOXA11-AS promotes the migration and invasion of hepatocellular carcinoma cells by inhibiting miR-124 expression by binding to EZH2 - Wen-long Zhang; Ya-nan Zhao; Zhang-zhen Shi; Gui-ying Gu; Dan Cong; Chen Wei; Yuan-song Bai (Human Cell, 2019)

High-temperature X-ray diffraction, Raman and IR spectroscopy on serandite - Yu Ye; Long Li; Joseph R. Smyth; Zhongping Wang; Dan Liu; Xiang Wang; Cao Wang (Physics and Chemistry of Minerals, 2019)

Life cycle assessment of oilseed crops produced in rotation with dryland cereals in the inland Pacific Northwest - Sharath Kumar Ankathi; Dan S. Long; Hero T. Gollany; Prajesh Das; David Shonnard (The International Journal of Life Cycle Assessment, 2019)

Treatment with MQA, a Derivative of Caffeoylquinic Acid, Provides Neuroprotective Effects against Cerebral Ischemia Through Suppression of the p38 Pathway and Oxidative Stress in Rats - Long Chen; Dan-ni Liu; Yu Wang; Xue-ying Liu; Shuai Han; Ke Zhang; Guo-yu Li; Xing Tian; Hang-yu Wang; Jin-hui Wang (Journal of Molecular Neuroscience, 2019)

New Waxy allele wx-Reina found in Chinese waxy maize - Xiaoyang Wu; Shaoyun Wu; Wenjie Long; Dan Chen; Guoyan Zhou; Juan Du; Qing Cai; Xingqi Huang (Genetic Resources and Crop Evolution, 2019)

Correction to: Life cycle assessment of oilseed crops produced in rotation with dryland cereals in the inland Pacific Northwest - Sharath Kumar Ankathi; Dan S. Long; Hero T. Gollany; Prajesh Das; David Shonnard (The International Journal of Life Cycle Assessment, 2019)

Morphology and multigene phylogeny reveal new genus and species of Torulaceae from freshwater habitats in northwestern Yunnan, China - Xi-Jun Su; Zong-Long Luo; Rajesh Jeewon; Darbhe J. Bhat; Dan-Feng Bao; Wen-Li Li; Yu-E Hao; Hong-Yan Su; Kevin D. Hyde (Mycological Progress, 2018)

Morphological and molecular taxonomy of novel species Pleurotheciaceae from freshwater habitats in Yunnan, China - Zong-Long Luo; Kevin D. Hyde; Darbhe J. Bhat; Rajesh Jeewon; Sajeewa S. N. Maharachchikumbura; Dan-Feng Bao; Wen-Li Li; Xi-Jun Su; Xiao-Yan Yang; Hong-Yan Su (Mycological Progress, 2018)

Transcriptome analysis of alternative splicing in different moso bamboo tissues - Long Li; Qianqian Shi; Dan Hou; Zhanchao Cheng; Juan Li; Yanjun Ma; Xueping Li; Shaohua Mu; Jian Gao (Acta Physiologiae Plantarum, 2018)

A20 prevents obesity-induced development of cardiac dysfunction - Wenjing Xu; Cheng Wang; Minglu Liang; Long Chen; Qin Fu; Fengxiao Zhang; Yan Wang; Dan Huang; Kai Huang (Journal of Molecular Medicine, 2018)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

A new catechin derivative from the fruits of Rosa sterilis S. D. Shi - Xu-Lu Luo; Han-Long Dan; Na Li; Yong-He Li; Ying-Jun Zhang; Ping Zhao (Natural Product Research, 2017)

An amplitude suppression method based on the decibel criterion - Xuan-Lin Kong; Hui Chen; Jin-Long Wang; Zhi-quan Hu; Dan Xu; Lu-Ming Li (Applied Geophysics, 2017)

Tolerance and stress response of sclerotiogenic Aspergillus oryzae G15 to copper and lead - Dan-Dan Long; Rong-Rong Fu; Jian-Rong Han (Folia Microbiologica, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Heat shock protein 90 is a stress and immune response gene in the giant spiny frog Quasipaa spinosa - Shu Miao-An; Tu Dan-Dan; Zhang Pan; Long Chen; Gu Wen-Bin; Zhou Zhong-Kai (Fisheries Science, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Evidence that ghrelin may be associated with the food intake of gibel carp (Carassius auratus gibelio) - Chaowei Zhou; Jinfa Zheng; Luo Lei; Dengyue Yuan; Chengke Zhu; Hua Ye; Chi Zhang; Dan Wang; Minmin Yang; Jingjing Wu; Long Zhu; Benhe Zeng (Fish Physiology and Biochemistry, 2016)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Neurofibromin Regulates Seizure Attacks in the Rat Pilocarpine-Induced Model of Epilepsy - Min Ren; Kunyi Li; Dan Wang; Jiamei Guo; Jing Li; Guang Yang; Xianghua Long; Wenjing Shen; Rong Hu; Xuefeng Wang; Kebin Zeng (Molecular Neurobiology, 2016)

Contra-directional Coupling of Nur77 and Nurr1 in Neurodegeneration: A Novel Mechanism for Memantine-Induced Anti-inflammation and Anti-mitochondrial Impairment - Xiaobo Wei; Huimin Gao; Jing Zou; Xu Liu; Dan Chen; Jinchi Liao; Yunqi Xu; Long Ma; Beisha Tang; Zhuohua Zhang; Xiang Cai; Kunling Jin; et al. (Molecular Neurobiology, 2016)

Sporoschisma from submerged wood in Yunnan, China - Zong-Long Luo; Dan-Feng Bao; Jayarama D. Bhat; Jing Yang; Hong-Mei Chai; Shu-Hong Li; Ali H. Bahkali; Hong-Yan Su; Kevin D. Hyde (Mycological Progress, 2016)

Sialylation and desialylation dynamics of monocytes upon differentiation and polarization to macrophages - Dan Wang; Evgeny Ozhegov; Lin Wang; Aimin Zhou; Huan Nie; Yu Li; Xue-Long Sun (Glycoconjugate Journal, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

Anthropogenic activities drive the microbial community and its function in urban river sediment - Xu Zhang; Qing Gu; Xi-En Long; Zhao-Lei Li; Dong-Xiu Liu; Dan-Hua Ye; Chi-Quan He; Xiao-Yan Liu; Kristiina Väänänen; Xue-Ping Chen (Journal of Soils and Sediments, 2016)

Erratum to: Identification and characterization of microRNAs at different flowering developmental stages in moso bamboo (Phyllostachys edulis) by high-throughput sequencing - Jian Gao; Wei Ge; Ying Zhang; Zhanchao Cheng; Long Li; Dan Hou; Chenglin Hou (Molecular Genetics and Genomics, 2015)

Identification and characterization of microRNAs at different flowering developmental stages in moso bamboo (Phyllostachys edulis) by high-throughput sequencing - Jian Gao; Wei Ge; Ying Zhang; Zhanchao Cheng; Long Li; Dan Hou; Chenglin Hou (Molecular Genetics and Genomics, 2015)

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation - Ji-Hong Liu; Qiang-Long You; Mei-Dan Wei; Qian Wang; Zheng-Yi Luo; Song Lin; Lang Huang; Shu-JI Li; Xiao-Wen Li; Tian-Ming Gao (Molecular Neurobiology, 2015)

Gadd45b Mediates Axonal Plasticity and Subsequent Functional Recovery After Experimental Stroke in Rats - Bin Liu; Long-ling Li; Xiao-dan Tan; Yan-hong Zhang; Ying Jiang; Guo-qian He; Qian Chen; Chang-qing Li (Molecular Neurobiology, 2015)

A Numerical Study of Water Loss Rate Distributions in MDCT-Based Human Airway Models - Dan Wu; Shinjiro Miyawaki; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2015)

On-combine, multi-sensor data collection for post-harvest assessment of environmental stress in wheat - Dan S. Long; John D. McCallum (Precision Agriculture, 2015)

Transcriptome profiling of trichome-less reveals genes associated with multicellular trichome development in Cucumis sativus - Jun-Long Zhao; Yun-Li Wang; Dan-Qing Yao; Wen-Ying Zhu; Long Chen; Huan-Le He; Jun-Song Pan; Run Cai (Molecular Genetics and Genomics, 2015)

Effects of glutamate on growth, antioxidant capacity, and antioxidant-related signaling molecule expression in primary cultures of fish enterocytes - Jun Jiang; Dan Shi; Xiao-Qiu Zhou; Long Yin; Lin Feng; Yang Liu; Wei-Dan Jiang; Ye Zhao (Fish Physiology and Biochemistry, 2015)

Spectral indices for yellow canola flowers - John J. Sulik; Dan S. Long (International Journal of Remote Sensing, 2015)

Mutation breeding of high 4-androstene-3,17-dione-producing Mycobacterium neoaurum ZADF-4 by atmospheric and room temperature plasma treatment - Chao Liu; Xian Zhang; Zhi-ming Rao; Ming-long Shao; Le-le Zhang; Dan Wu; Zheng-hong Xu; Hui Li (Journal of Zhejiang University-SCIENCE B, 2015)

Editorial: Quaternary revolutions - DAN J. CHARMAN; GEOFF A. T. DULLER; ANTONY J. LONG; DANIELLE C. SCHREVE; JAMES D. SCOURSE (Journal of Quaternary Science, 2015)

Induction of autophagy in human neuroblastoma SH-SY5Y cells by tri-ortho-cresyl phosphate - Ding-Xin Long; Dan Hu; Pan Wang; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2014)

Calcitonin Gene-Related Peptide Inhibits Osteolytic Factors Induced by Osteoblast In Co-Culture System with Breast Cancer - Hui Zhao; Lin-lin Ning; Zhi-yu Wang; Hong-tao Li; Dan Qiao; Yang Yao; Huan-long Qin (Cell Biochemistry and Biophysics, 2014)

Erratum to: Physiological and metabolic analysis of nitrate reduction on poly-gamma-glutamic acid synthesis in Bacillus licheniformis WX‑02 - Xin Li; Xiangyong Gou; Dan Long; Zhixia Ji; Lifang Hu; Dihong Xu; Jun Liu; Shouwen Chen (Archives of Microbiology, 2014)

Physiological and metabolic analysis of nitrate reduction on poly-gamma-glutamic acid synthesis in Bacillus licheniformis WX-02 - Xin Li; Xiangyong Gou; Dan Long; Zhixia Ji; Lifang Hu; Dihong Xu; Jun Liu; Shouwen Chen (Archives of Microbiology, 2014)

Change of floral orientation affects pollinator diversity and their relative importance in an alpine plant with generalized pollination system, Geranium refractum (Geraniaceae) - Hui Wang; Chang-Long Xiao; Robert W. Gituru; Zheng Xiong; Dan Yu; You-Hao Guo; Chun-Feng Yang (Plant Ecology, 2014)

A Numerical Study of Heat and Water Vapor Transfer in MDCT-Based Human Airway Models - Dan Wu; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2014)

Bioactive Equivalence of Combinatorial Components Identified in Screening of an Herbal Medicine - Peng Liu; Hua Yang; Fang Long; Hai-Ping Hao; Xiaojun Xu; Ying Liu; Xiao-Wei Shi; Dan-Dan Zhang; Hao-Chuan Zheng; Qian-Ying Wen; Wen-Wen Li; Hui Ji; et al. (Pharmaceutical Research, 2014)

Effect of copper-induced oxidative stress on sclerotial differentiation and antioxidant properties of Penicillium thomii PT95 strain - Ze-Qing Zhang; Wen-Jing Zhao; Dan-Dan Long; Lin-Ru Niu; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2014)

Evaluation of 10 year AQUA/MODIS land surface temperature with SURFRAD observations - Sanmei Li; Yunyue Yu; Donglian Sun; Dan Tarpley; Xiwu Zhan; Long Chiu (International Journal of Remote Sensing, 2014)

Subtractive screen of potential limb regeneration related genes from Pachytriton brevipes - Dan Jiang; Xiao-Long Zhu; Jun-Fang Zhao; Yan-Kuan Zhou; Chao Zhong; Ji Zhang; Xiao Huang (Molecular Biology Reports, 2014)

A study of a rare chromosomal disorder: mosaic 46,XX,del(18)(p11.2)/46,XX,i(18q) - DAN PENG; PAN-PAN LONG; BO WEN; RONG-HUI YU (Journal of Genetics, 2013)

Isolation and characterization of microsatellite loci in the short-tailed pit viper Gloydius brevicaudus (Viperidae) - Li Ma; Qing-Lin Tong; Ce Chen; Ying-Dan Pan; Long-Hui Lin (Conservation Genetics Resources, 2013)

Remote Sensing for sustainable agriculture - Maxim Shoshany; Dan Long; David Bonfil (International Journal of Remote Sensing, 2013)

Mapping straw yield using on-combine light detection and ranging (lidar) - Dan S. Long; John D. McCallum (International Journal of Remote Sensing, 2013)

TiO2/T-PVA Composites Immobilized on Cordierite: Structure and Photocatalytic Activity for Degrading RhB Under Visible Light - Jianling Zhang; Yuanqing Song; Haigang Yang; Shoubin Xu; Long Jiang; Yi Dan (Water, Air, & Soil Pollution, 2013)

Air pollution and admissions for acute lower respiratory infections in young children of Ho Chi Minh City - Sumi Mehta; Long H. Ngo; Do Van Dzung; Aaron Cohen; T. Q. Thach; Vu Xuan Dan; Nguyen Dinh Tuan; Le Truong Giang (Air Quality, Atmosphere & Health, 2013)

Identification and characterization of the soybean IPK1 ortholog of a low phytic acid mutant reveals an exon-excluding splice-site mutation - Feng-Jie Yuan; Dan-Hua Zhu; Yuan-Yuan Tan; De-Kun Dong; Xu-Jun Fu; Shen-Long Zhu; Bai-Quan Li; Qing-Yao Shu (Theoretical and Applied Genetics, 2012)

Culture-independent characterization of the autochthonous gut microbiota of grouper Epinephelus coioides following the administration of probiotic Enterococcus faecium - Yun-Zhang Sun; Hong-Ling Yang; Ru-Long Ma; Kun-Peng Huang; Ji-Dan Ye (Aquaculture International, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Dietary selenium regulation of transcript abundance of selenoprotein N and selenoprotein W in chicken muscle tissues - Jiu-li Zhang; Jin-Long Li; Xiao-dan Huang; Sun Bo; Wang Rihua; Shu Li; Shi-wen Xu (BioMetals, 2012)

Enhanced biodesulfurization by expression of dibenzothiophene uptake genes in Rhodococcus erythropolis - Ze-long Wang; Dan Wang; Qiang Li; Wang-liang Li; Huang Tang; Jian-min Xing (World Journal of Microbiology and Biotechnology, 2011)

The influence of genetic polymorphisms and interacting drugs on initial response to warfarin in Chinese patients with heart valve replacement - Shi-Long Zhong; Yuan Liu; Xi-Yong Yu; Dan Xu; Hong-Hong Tan; Qiu-Xiong Lin; Min Yang; Hai-Yan Lao; Shu-Guang Lin (European Journal of Clinical Pharmacology, 2011)

Mineral status and mechanical properties of cancellous bone exposed to hydrogen peroxide for various time periods - Dan Li; Long Bi; Guolin Meng; Jun Wang; Rong Lv; Min Liu; Jian Liu; Yunyu Hu (Cell and Tissue Banking, 2011)

Visible Light Induced Photocatalytic Degradation of Methyl Orange by Polythiophene/TiO2 Composite Particles - Shoubin Xu; Yunfeng Zhu; Long Jiang; Yi Dan (Water, Air, & Soil Pollution, 2010)

Multi-variety bone bank in China - Dan Li; Long Bi; Guo-Lin Meng; Min Liu; Jing Jin; Yin Liu; Zhen Wang; Jian Liu; Yun-Yu Hu (Cell and Tissue Banking, 2010)

Implementation and Comparison of Reservoir Operation Strategies for the Hoa Binh Reservoir, Vietnam using the Mike 11 Model - Long Le Ngo; Henrik Madsen; Dan Rosbjerg; Claus B. Pedersen (Water Resources Management, 2008)

Soil Phosphorus and Potassium Mapping Using a Spatial Correlation Model Incorporating Terrain Slope Gradient - Brian Kozar; Rick Lawrence; Dan S. Long (Precision Agriculture, 2002)

Identification of human CDV-1R and mouse Cdv-1R, two novel proteins with putative signal peptides, especially highly expressed in testis and increased with the male sex maturation - Jisong Peng; Long Yu; Masahisa Horiuchi; Pingzhao Zhang; Xinghua Huang; Yazhou Zhang; Dan Li; Md Abdul Jalil; Shouyyan Zhao (Molecular Biology Reports, 2002)

Method for Precision Nitrogen Management in Spring Wheat: II. Implementation - Dan S. Long; Richard E. Engel; Gregg R. Carlson (Precision Agriculture, 2000)

Method for Precision Nitrogen Management in Spring Wheat: I Fundamental Relationships - Richard E. Engel; Dan S. Long; Gregg R. Carlson; Corey Meirer (Precision Agriculture, 1999)